Instructor Adoption of E-learning Systems in Tanzania’s Universities: A Proposed Multi-Factors Adoption Model (MFAM11) - Deogratius Mathew Lashayo; Md Gapar Md Johar (JOIV : International Journal on Informatics Visualization, 2018)
Current studies show that there is no comprehensive adoption model in e-learning systems in universities. This problem opens up to too much debates about which models and frameworks fit well in an e-learning environment particularly in universities in Tanzania. This paper answers the two debatable questions, which are:(1) what are the factors that affect adoption of e-learning systems in Tanzania’s universities, (2) what is the comprehensive e-learning adoption model in universities in Tanzania. This research study adapts DeLone and McLean (2003) IS model after an extensive literature reviews conducted in information systems and in e-learning systems. The findings from this research will add up to literature of limited factors’ model and it will open it up for validation in a different universities’ application domain.